Metrical invariants and covariants of couples of planes in the flag space - Rozenfeld, B. A.; Ezhova-Guseva, L. M.; Semenova, T. A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. А. Розенфельд, Л. М. Ежова-Гусева и Т. А. Семенова. Метрические инварианты и коварианты пар плоскостей во флаговом пространстве B. A. Rozenfeldas, L. M. Ežova-Guseva, T. A. Semionova. Flaginės erdvės plokštumų dvejetų metriniai kovariantai ir invariantai